Advances in ultrasonography and radiologic diagnosis of pulmonary arteriovenous fistula associated with cryptogenic stroke - CHEN Yu⁃jun; CHEN Hong⁃xiu; XING Ying⁃qi (Chinese Journal of Contemporary Neurology and Neurosurgery)
Cryptogenic stroke (CS) is a type of ischemic stroke with an unknown cause, and it is closely associated with right⁃to⁃left shunt (RLS). Patent foramen ovale (PFO) and pulmonary arteriovenous fistula (PAVF) are two common types of RLS. While there has been extensive research on PFO, there has been relatively less attention paid to PAVF. Writer provides a review of the clinical features, advances in ultrasonography and imaging diagnostic techniques, as well as treatment methods and prognosis analysis of PAVF, with the aim of providing reference for clinical practice.